Prevalence of Bovine Haemoparasites and Risk Factors Associated with Trypanosoma Evansi Infection in Malaysia - Md Isa, Nur Mahiza (2010)
A cross sectional study was carried out in Peninsular Malaysia to determine the prevalence and intensity of bovine haemoparasites, and to investigate the spatial distribution, seroprevalence and the risk factors associated with Trypanosoma evansi infection. A total of eleven farms were sampled throughout the country involving 1562 heads of cattle from seven breeds. Blood and serum were collected from each animal in order to determine the parasitological prevalence of haemoparasties and the seroprevalence of T. evansi respectively. Giemsa-stained thin blood films were prepared and examined for haemoparasites. Theleria sp. was the most prevalent haemoparasite, being present in 16.4% of the cattle, followed by Mycoplasma sp. (11.2%), T. evansi (0.6%), Anaplasma marginale (0.1%) and Babesia bigemina (0.1%). The highest prevalence and intensity of haemoparasite infection were found in the imported Nelore and Mafriwal breeds. In contrast, the local Kedah Kelantan (KK) was found to have lower prevalence and intensities of the same organisms. In order to determine the spatial distribution and seroprevalence of T. evansi, Peninsular Malaysia was stratifed into six geographical zones. Haematocrit Centrifugation Technique (HCT) and the CATT/T. evansi kit were employed to detect active parasitaemia and circulating anti-RoTat1.2 antibodies specific for T. evansi, respectively. In order to qualify the use of the CATT/T. evansi kit, 41 field isolates of T. evansi were screened by PCR for the presence of the RoTat1.2 VSG gene within the genome. Molecular analysis revealed that all the local isolates examined possessed the said gene, rendering the CATT/IT. evansi kit valid for serodiagnosis. The overall parasitological prevalence of T. evansi in the country was 2.1% while the seroprevalence was 52.0%, much higher than previously assumed. The highest parasitaemia and seroprevalence was found in the southeastern (4.5%) and southwestern (73.1%) zones, respectively. The risk factors associated with local bovine T. evansi infection was also identified by collating data from direct observations and structured questionnaires. Using binary logistic regression analyses, the cattle breed was identified as a significant risk factor for parasitaemia, while the breed, age, sex and cattle production type were identified as significant risk factors for the presence of circulating anti-T. evansi antibodies. Higher risk of active T. evansi infection was found in the Nelore and Droughtmaster, while the Jersey crosses, Mafriwal and Friesian crosses have a higher risk of seropositivity. In conclusion, bovine haemoparasites are widespread in Peninsular Malaysia with different prevalences between the various zones. All local T. evansi isolates examined possess the RoTat 1.2 VSG gene, qualifying the use of the CATT/T. evansi kit locally. Cattle in Peninsular Malaysia are exposed to a number of pathogenic and economically important haemoparasites, with the imported exotic breeds showing a higher susceptibility compared to the indigenous KK cattle. From the parasitological viewpoint, it is apparent that the KK and its crosses maybe more suitable to develop in order to meet the demands of the expanding local beef industry.